Adapting to Remote Teaching: Experiences and Technological Adjustments of Rural Physical Science Teachers During the COVID-19 Pandemic - Photo, Patricia; Mohale, Thabiso Melvar (Research in Social Sciences and Technology, 2024)
The COVID-19 pandemic necessitated an abrupt shift to remote teaching, presenting unique challenges for rural Physical Science teachers due to their limited access to technological resources. This qualitative study employed a phenomenological approach to explore the lived experiences of six Physical Science teachers from rural South Africa during this transition. Data were gathered through semi-structured interviews, classroom observations, and document analysis. The findings reveal significant disruptions in teaching and learning processes, with a pronounced negative impact on student engagement and learning outcomes. The study highlights teachers’ adaptative measures, including using WhatsApp and other digital platforms to mitigate educational interruptions. Despite their efforts, the lack of infrastructure and digital tools severely restricted effective teaching. This research highlights the necessity of enhanced technological support and resources for rural educators to ensure resilient and adaptable educational practices in the face of future disruptions. The experiences detailed herein reflect broader implications for policy and practice, advocating for a strategic focus on closing the digital divide and supporting rural educators comprehensively.